2015
DOI: 10.1007/s11547-015-0590-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution computed tomography and rheumatoid arthritis: semi-quantitative evaluation of lung damage and its correlation with clinical and functional abnormalities

Abstract: It is considered that this semi-quantitative method may have added value in early diagnosis, appropriate treatment decisions and follow-up when taken into account together with risk factors associated with pulmonary damage in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
5
4
0
3
Order By: Relevance
“…Our study failed to find any association between smoking and pulmonary abnormalities. In agreement with our study, Sakre et al (7) found no association to smoking Bilgici et al (13) stated that smoking was not associated with physiological or HRCT abnormalities suggestive of RA ILD Zhang et al (11) . concluded that smoking is a significant risk factor for the development of ILD in RA patients .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study failed to find any association between smoking and pulmonary abnormalities. In agreement with our study, Sakre et al (7) found no association to smoking Bilgici et al (13) stated that smoking was not associated with physiological or HRCT abnormalities suggestive of RA ILD Zhang et al (11) . concluded that smoking is a significant risk factor for the development of ILD in RA patients .…”
Section: Discussionsupporting
confidence: 93%
“…Results of Sakre et al (20) . Bilgici et al (7) agreed with us and found no association with medications (20) (7). This result suggests that changes detected by HRCT may occur as a result of RA associated factors rather than treatment given.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…[3][4][5][6] Bu genifl aral›¤›n nedeni altta yatan BDH ve ‹AH tan›s› için kullan›lan tan›sal yöntemin farkl›l›¤›d›r. Tan› için kullan›lan yönteme göre s›kl›k de¤iflmektedir; özellikle radyolojik yöntemler kullan›ld›¤›n-da s›kl›k daha da yüksek de¤erlere ulaflmaktad›r.…”
Section: Prevalans Ve Risk Faktörleriunclassified
“…Oysa ‹AH tan›s› için solunum fonksiyon testleri (SFT) ve karbonmonoksit difüzyon kapasitesi (DLCO) kullan›ld›¤›nda bu s›kl›k %40'lara, yüksek çözünürlüklü bilgisayarl› tomografi (HRCT) ile %60-80'lere ç›kmakta, akci¤er biyopsisi yap›lan serilerde ise bu oran %80'lere varmaktad›r. [1,2,4] Benzer flekilde sistemik sklerozda (SSc) akci¤er biyopsisi yap›lan serilerde s›kl›k %60-90 iken sadece klinik bulgular baz ald›¤›nda s›kl›k %26, akci¤er grafisi baz al›nd›¤›nda ise %22 olarak bildirilmifltir. [1,2,5] Altta yatan BDH göre s›kl›¤a bak›ld›¤›nda genel olarak en s›k SSc'de, en az s›k-l›kta ise sistemik lupus eritematozusta (SLE) ‹AH saptand›¤› görülmektedir (Tablo 1).…”
Section: Prevalans Ve Risk Faktörleriunclassified